Integrasi ESG dalam e-Procurement : Solusi untuk Pengadaan Berkelanjutan di Indonesia - Ardiansyah S. Akili; Fitryane Lihawa; Dewi Wahyuni K. Baderan (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
E The integration of Environmental, Social, and Governance (ESG) principles into e-procurement systems offers a pathway to achieving sustainable public procurement in Indonesia. This study explores relevant ESG criteria and formulates strategies to enhance the capacity of procurement personnel in implementing these principles. The findings highlight the importance of incorporating environmental criteria such as energy efficiency, eco-friendly materials, and waste management; social criteria like labor standards compliance, local MSME empowerment, and gender equality; and governance criteria including transparency, anti-corruption, and tax compliance. While e-procurement provides a digital platform to improve efficiency and transparency, challenges such as limited awareness, capacity gaps, and the absence of specific ESG guidelines hinder effective implementation. To address these issues, the study proposes strategic measures, including the development of ESG-based evaluation systems, comprehensive training programs for procurement personnel, and robust monitoring frameworks. These initiatives aim to align procurement practices with the principles of Sustainable Public Procurement (SPP), ensuring that procurement contributes to environmental sustainability, social equity, and better governance. By overcoming existing barriers and fostering collaboration among stakeholders, Indonesia can position itself as a leader in sustainable procurement practices. This research provides practical recommendations to integrate ESG into procurement systems, paving the way for a more accountable, equitable, and sustainable procurement framework.